FLIPBOOK LEARNING MEDIA ON IPAS LEARNING OUTCOMES IN ELEMENTARY SCHOOL STUDENTS - Elma Maylisa Wahyu Salsabila; Suryanti Suryanti; Wahono Widodo; Ganes Gunansyah; Ari Metalin Ika Puspita (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze the effect of Flipbook as a learning medium on elementary school students' Ilmu Pengetahuan Alam dan Sosial (IPAS) learning outcomes through a literature review. Flipbook is an interactive digital learning medium that enhances students' engagement and understanding of the subject matter. This research employs a literature review method by analyzing previous studies discussing Flipbook effectiveness in learning. The findings indicate that Flipbook positively impacts students' learning outcomes, as evidenced by increased pretest and posttest scores. Additionally, Flipbook supports various learning models such as Jigsaw and Problem-Based Learning (PBL), improving learning effectiveness. The analysis also reveals that Flipbook significantly enhances students' learning interest, conceptual understanding, and academic achievement. Therefore, the use of Flipbook as a learning medium in elementary schools is highly recommended to foster more interactive and effective learning.